A Rare Case of Spontaneous Arachnoid Cyst Rupture Presenting as Right Hemiplegia and Expressive Aphasia in a Pediatric Patient - Anne Bryden; Natalie Majors; Vinay Puri; Thomas Moriarty (MDPI AG, 2021)
This study examines an 11-year-old boy with a known history of a large previously asymptomatic arachnoid cyst (AC) presenting with acute onset of right facial droop, hemiplegia, and expressive aphasia. Shortly after arrival to the emergency department, the patient exhibited complete resolution of right-sided hemiplegia but developed headache and had persistent word-finding difficulties. Prior to symptom onset while in class at school, there was an absence of reported jerking movements, headache, photophobia, fever, or trauma. At the time of neurology consultation, the physical exam showed mildly delayed cognitive processing but was otherwise unremarkable. The patient underwent MRI scanning of the brain, which revealed left convexity subdural hematohygroma and perirolandic cortex edema resulting from ruptured left frontoparietal AC. He was evaluated by neurosurgery and managed expectantly. He recovered uneventfully and was discharged two days after presentation remaining asymptomatic on subsequent outpatient visits. The family express concerns regarding increased anxiety and mild memory loss since hospitalization.